A Novel Multi-articular Leg Mechanism for Biped Robots Inspired by Bi-articular Muscle - Lee, Jongwoo; Lee, Giuk; Hong, Seokmin; Lee, SangWook; Kim, Jung Hoon; Oh, Yonghwan (2016 6TH IEEE INTERNATIONAL CONFERENCE ON BIOMEDICAL ROBOTICS AND BIOMECHATRONICS (BIOROB), 2016)
This paper proposes a novel multi-articular leg system for biped robot. The structure and actuation scheme of the mechanism are inspired by redundantly-actuated manipulators, of which actuators span over multiple joints like bi-articular muscles. The proposed mechanism for robotic leg contributes to improved capacity in end-effector force exertion, which allows less performance requirements in individual actuators. For the purpose of evaluation, we provide the static torque-force transmission analysis, as well as walking simulation results conducted in the dynamic simulator. The results indicate that the proposed mechanism can benefit from the improved output force capacity.